Perceptions and General Knowledge of Online Social Networking Activity of University Student-Athletes and Non-Student-Athletes - Cody T. Havard; Terry Eddy; Lamar Reams; Rebecca L. Stewart; Tariq Ahmad (Journal of Applied Sports Management, 2013)
The current study investigated differences between student-athletes and non-student-athletes regarding online social networking (OSN) usage. In particular, types of usage, perceptions of monitoring, and knowledge and perceptions of inappropriate online behavior were examined. Participants were student-athletes and non-student-athletes at a mid-sized university in the Rocky Mountain Region, who were asked their perceptions regarding OSN. Results of independent samples t-tests revealed student-athletes felt that students in general were more knowledgeable of the dangers associated with OSN than were non-studentathletes. Further, student-athletes found provocative pictures posted on OSN profiles to be more acceptable than did non-student-athletes. Also, monitoring of online profiles by supervisory figures was considered less acceptable to student-athletes than non-studentathletes. Theoretical and practical implications are discussed.
Keywords: online social networking; Facebook; student-athletes; online social networking education; online social networking usage; athletic administration; online profile monitoring; social capital.